EKSISTENSI HAK KEKEBALAN DIPLOMATIK TERHADAP PELANGGARAN HUKUM SEORANG DIPLOMAT DALAM KACAMATA HUKUM INTERNASIONAL DAN YURISDIKSI NEGARA PENERIMA - Dwi Nuryani; Cinde Salsabiil; Happy Herlambang (Magister Hukum Sekolah Pascasarjana Unida, 2022)
The purpose of this study is to determine the ideal law enforcement for foreign diplomats who commit violations or crimes in the receiving country. Then also to find out the implementation of law enforcement against criminal cases committed by US diplomats (2017) and Malaysian diplomats (2014) in New Zealand. The normative juridical method and qualitative analysis are the research methods used in this paper, namely collecting data relevant to the issues to be discussed and then linked to one another in order to obtain conclusions. All data obtained in this paper are sourced from relevant legal sources, books, journal articles, and other literature. The data obtained is secondary which is processed to obtain conclusions. The results of this study indicate that the receiving country has the authority to carry out Persona Non-Grata to diplomats who are considered incapable or fail in carrying out their duties in their country such as in terms of law violations/crimes so that the sending country needs to ensure that its Diplomat Officers are people who are able to carry out their duties and missions. and carry the name of his country and ensure that no immunity rights are abused. The receiving country must be selective about determining who is right and appropriate to be a representative of another country entering the country, this is for the security and comfort of the country.